Women classical scholars : unsealing the fountain from the Renaissance to Jacqueline de Romilly - Hall, Edith; Hall, Edith; Wyles, Rosie; Wyles, Rosie (Classical presences, 2016)
This volume celebrates the women born between the Renaissance and 1913 who played significant roles in the history of classical scholarship. Synthesising incisive case-studies with overviews of the evolution of the discipline, it explores their legacy and provides scholars of today with the female intellectual ancestors they did not know they had